Melatonin promotes sirtuin 1 expression and inhibits IRE1α–XBP1S–CHOP to reduce endoplasmic reticulum stress–mediated apoptosis in chondrocytes - Qin, Kunpeng; Tang, Hao; Ren, Yi; Yang, Di; Li, Yetian; Huang, Wei; Wu, Yunfeng; Yin, Zongsheng (Frontiers in Pharmacology, 2022)
Osteoarthritis (OA) is the most common chronic disease characterized by the loss of chondrocytes and the degeneration of cartilage. There are many pathogenic factors of OA; In particular, however, inflammation plays an important role in the pathogenesis and progression of OA via the activation of endoplasmic reticulum (ER) stress signaling pathway. In this study, we stimulated human primary chondrocytes with lipopolysaccharides (LPS) to reduce cell viability and induce chondrocyte apoptosis. LPS–stimulated human primary chondrocytes induced ER stress and significantly upregulated the ER chaperone glucose–regulated protein 78 (GRP78) and increased the expression level of C/EBP–homologous protein (CHOP), a key mediator of ER stress––induced apoptosis. Interestingly, melatonin treatment attenuated ER stress–mediated chondrocyte apoptosis. Melatonin inhibited the expression of cleaved caspase–3, Bax, CHOP, GRP78, phospho–inositol–requiring enzyme 1α (P-IRE1α), and spliced X–box–binding protein 1 (XBP1S). Our anterior cruciate ligament transection (ACLT) mouse model of OA showed that melatonin (50 and 150 mg/kg) dose–dependently relieved joint cartilage degeneration in OA mice and experienced an inhibition of chondrocyte apoptosis. Immunohistochemical analysis showed that melatonin could promote the expression of SIRT 1 and inhibit the expressions of CHOP and cleaved caspase–3 in OA mice. In conclusion, our findings demonstrate for the first time that melatonin inhibited the IRE1α–XBP1S–CHOP signaling axis by promoting the expression of SIRT1 in LPS–treated human chondrocytes and delaying OA progression in vivo.